HUBUNGAN DUKUNGAN SUAMI DENGAN TINGKAT KECEMASAN IBU HAMIL TRIMESTER III - Nur Fatimah Az Zahro, Aulia; Wahyuntari , Evi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Anxiety in pregnant women in the third trimester can negatively impact the mother's psychological condition and can endanger the health of both mother and fetus, one of which is influenced by the support of the husband or family. This observational analytical study employed a cross-sectional study design. 77 respondents were selected using total sampling. Data were collected using a husband's support questionnaire and an anxiety questionnaire, the PASS (Perinatal Anxiety Screening Scale). Data analysis performed using the Chi-Square statistical test yielded a p-value of 0.003 (p<0.05), indicating a relationship between husband's support and anxiety levels of pregnant women in the third trimester. The results of the study, which included 77 respondents; showed that the majority of respondents, 47 respondents (61.0%), were in the supportive husband category. Meanwhile, 26 (33.8%) were in the no anxiety category. Pregnant women in their third trimester who received support from their husbands tended to minimize anxiety compared to those who lacked support. It is recommended that pregnant women in their third trimester pay attention to their physical and psychological condition and ask their husbands to provide constant support, prepare for childbirth, and participate in maintaining the pregnancy.